Source identification and distribution reveals the potential of the geochemical Antarctic sea ice proxy IPSO25 - S. T. Belt (Nature Portfolio, 2016)
The sedimentary presence of the diatom lipid diene II (hereafter IPSO25) has been proposed as a proxy for palaeo Antarctic sea ice. Here, the authors identify a source of IPSO25and hypothesize that its sedimentary distribution may provide proxy evidence of landfast ice influenced by freshwater discharge.